INVENTORY OF MACROINVERTEBRATES FROM SOME REGIONS OF SOUK AHRAS - KHOUALDIA Rania; TOUAFCHIA Nariman (My University, 2024)
Water plays a crucial role in our planet's regulation and is now both valuable and scarce. Benthic macroinvertebrate species inhabit ocean depths and rivers and lakes, dispersing based on environmental factors. A study on macroinvertebrate species was conducted in 3 lentic ecosystem during the period of November 2023 to May 2024 to evaluate the diversity of macroinvertebrates at different aquatic environments in the Souk-Ahras region wich is Burgas lakes, Ain Tamtmat dam and Ain Dalia dam. In addition, 5 physicochemical variables of the water were measured (temperature; electrical conductivity; salinity; Hydrogen potential and depth) and the Shannon H and equitabilite indices to evaluate the hydro-biological quality of the water The collected individuals were divided into four class with seven zoological orders and 13 families, ----------------------------------------------------------------------------------------------------------------------- يلعب الماء دورا حاسماً في تنظيم جميع أشكال الحياة على كوكبنا و في الوقت الحاضر تعيش أنواع اللافقريات الكبيرة القاعية في أعماق المحيطات و الأنهار و البحيرات و تنتشر بناءً على العوامل البيئية و هي الأن ذات قيمة و نادرة . اجريت دراسة على أنواع الافقريات الكبيرة في ثلاث أنظمة بيئية خلال فترة ممتدة من نوفمبر إلى ماي لتقييم تنوع اللافقريات الكبيرة في البيئات المائية المختلفة في منطقة سوق أهراس و هي بحيرات بورغاس سد طمطمات و سد عين الدالية بالإضافة إلى ذلك تم قياس متغيرات فيزياوكيميائية للمياه (درجة الحرارة ’ توصيل الكهربائي’ الملوحة و هيدروجينية المياه) و كذلك مؤشر شانون و مؤشرات التوازن لتقييم الجودة الهيدروبيولوجية للمياه. تم تقسيم العينات إلى أربع عائلات و سبع رتب و ثلاث عشر عائلة. ------------------------------------------------------------------------------------------------------------------------- L'eau joue un rôle crucial dans la régulation de notre planète et est aujourd'hui à la fois précieuse et rare. Les espèces de macroinvertébrés benthiques habitent les profondeurs des océans, les rivières et les lacs, et se dispersent en fonction de facteurs environnementaux. Une étude sur les espèces de macroinvertébrés a été menée dans 3 écosystèmes lentiques au cours de la période de novembre 2023 à mai 2024 pour évaluer la diversité des macroinvertébrés dans différents milieux aquatiques de la région de Souk-Ahras, à savoir les lacs de Bourgas, le barrage d'Ain Tamtmat et le barrage d'Ain Dalia. De plus, 5 variables physicochimiques de l'eau ont été mesurées (température ; conductivité électrique ; salinité ; Potentiel hydrogène et profondeur) ainsi que les indices Shannon H et équitabilité pour évaluer la qualité hydro-biologique de l'eau. Les individus collectés ont été divisés en quatre classes avec sept ordres zoologiques et 13 familles,